Naked-eye observations of visible spectra using a transmission-grating-based spectrometer. (24th June 2021) - Lin, Shan; Yang, Qingxin; Liu, Weilong; Wang, Xiaoou; Li, Junqing; Zhao, Haifa
Abstract: Naked-eye observations of visible spectra using a transmission-grating-based spectrometer, with the spectral resolution of 0.2 nm @ 550 nm, are reported in this article. The resultant accuracy of the wavelength readout with the naked-eye is better than 1 nm. The diffraction angles are precisely confirmed when the virtual diffraction image of the entrance slit (line spectrum) are collinear with two collimating slits. Furthermore, a converging lens is used to magnify the tiny light source (or narrow slit), and receive more radiant flux, with no effect on the accuracy of the spectral measurement. The spectrometer provides a good training aid for college students because (1) it is a low cost and handy demo experiment; (2) it has no optoelectronic sensor, it is completely naked-eye observation; (3) it helps students intuitively understand the diffracting and imaging processes; (4) the resolving power meets the requirements for teaching purposes.